DUKUNGAN SUAMI TERHADAP DETEKSI DINI KANKER SERVIKS PADA PASANGAN USIA SUBUR (PUS) DI DUSUN NGASEM DESA TIMBULHARJO SEWON BANTUL TAHUN 2016 - Fatimah Dewi Anggraeni; Klesia Benedikta (MEDIA ILMU KESEHATAN, 2016)
Background: One of the purposes of Sustainable Development Goals (SDGs) is promoting health with a target to reduce one-third of deaths from non-communicable diseases through prevention. Cervical cancer is a malignant tumor that grows in the cervix or uterus that comes from 90% of squamous cells lining the cervix and the remaining 10% comes from mucus-producing gland cells in the cervical canal leading into the uterus. Cervical cancer is the second killer of women worldwide after breast cancer. One effort to reduce cervical cancer is by conducting an early detection. Objectives: To investigate husbands’ support for early detection of cervical cancer in fertile-aged couples in Ngasem Timbulharjo Sewon Bantul Methods: This research was descriptive quantitative, with accindental sampling, involving 30 respondents aged 15-49 years old. Data were collected with a questionnaire and were analyzed using univariate analysis. Results: Husbands’ informational support was in low category (66.7%), assesment support was low (60.0%), instrumental support was low (53.3%), and emotional support was also low (63.3%). Conclusion: Husbands’ supports for early detection of cervical cancer were all in the low category. Keywords: Husband’s Support, Early Detection of Cervical Cancer